Simulation of energy consumption processes at the metallurgical enterprises in the energy-saving projects implementation - Kiyko S. G.; Druzhinin E. A.; Prokhorov O. V.; Haidabrus B. V. (Журнал інженерних наук)
The features of improving energy efficiency at a metallurgical enterprise based on portfolio management of energy-saving projects are considered. A simulation model of energy consumption at the metallurgical enterprise, which covers the entire metal products manufacture process, has been developed. The parameters, conduct, and visualization of simulation models of the main equipment such as an electric arc furnace and a ladle furnaces are described. With this software package’s help, a comparison of the permissible values and the adjusting of the predicted consumption of active power by a metallurgical enterprise for each fixed point in time are carried out. The system calculates the operating mode regulation range of electric arc furnaces to ensure the continuity of steel casting during melting of a particular steel grade along the appropriate technological routes. The model likewise includes algorithms for transport equipment management that minimize disruptions in continuous casting machines’ operation and simulate emergencies. The analysis of the results of energy consumption processes simulation at the metallurgical enterprise is carried out. As a result of modeling, it was possible to increase the productivity of a group of electric arc furnaces and ladle furnaces and reduce the maximum consumption of active power by the metallurgical enterprise. Experimental studies of energy consumption planning methods have been carried out based on real data on the metal products manufacture and electrical energy consumption by the production units of PJSC “Electrometallurgical plant “Dniprospetsstal”. The use of the electrical energy consumption model allows in an integrated manner and responds to the dynamics of production processes to carry out further calculations of economic feasibility studies, analysis, and selection of options for the project’s implementation of an energy-saving portfolio at the metallurgical enterprise.